Proposed Data Quality Evaluation Method For A Transportation Agency - Fatimah Mohamad Yunus; Pritheega Magalingam; Nurazean Maarop; Ganthan Narayana Samy; Doris Hooi-Ten Wong; Bharanidharan Shanmugam; Sundresan A/L Perumal (Universiti Teknologi Malaysia Press, 2024)
Non-Indexed Publication